2021
DOI: 10.1038/s41598-021-96018-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of new intragenic HBB haplotypes model for the prediction of beta-thalassemia in the Malaysian population

Abstract: This study sought to determine the potential role of HBB haplotypes to predict beta-thalassemia in the Malaysian population. A total of 543 archived samples were selected for this study. Five tagging SNPs in the beta-globin gene (HBB; NG_000007.3) were analyzed for SNP-based and haplotype association using SHEsis online software. Single-SNP-based association analysis showed three SNPs have a statistically significant association with beta-thalassemia. When Bonferroni correction was applied, four SNPs were foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the Thai population, the wild type was found to have high levels of heterogeneity in codon 2 (C/T), IVS II-16 (C/G) and the Hinf I polymorphism, with a minor allele frequency (MAF) of more than 30%, whereas IVS II-74 (G/T) and IVS II-81 (C/T) were found to have the least heterogeneity (MAF < 5%). However, two intragenic polymorphisms (IVS II-74 (G/T) and IVS II-81 (C/T)) have been found to have high levels of heterogeneity in other populations [ 13 , 14 , 23 ]. We compared the β-thalassemia genotype and wild type in each DAF of polymorphisms using the Fisher’s exact test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Thai population, the wild type was found to have high levels of heterogeneity in codon 2 (C/T), IVS II-16 (C/G) and the Hinf I polymorphism, with a minor allele frequency (MAF) of more than 30%, whereas IVS II-74 (G/T) and IVS II-81 (C/T) were found to have the least heterogeneity (MAF < 5%). However, two intragenic polymorphisms (IVS II-74 (G/T) and IVS II-81 (C/T)) have been found to have high levels of heterogeneity in other populations [ 13 , 14 , 23 ]. We compared the β-thalassemia genotype and wild type in each DAF of polymorphisms using the Fisher’s exact test.…”
Section: Discussionmentioning
confidence: 99%
“…Only two DNA polymorphisms on 3′ haplotypes are useful for studying the genetic background of β-globin genes: Ava II (IVS II-16) (rs10768683; C > G), located on the β-globin gene, and Hinf I (rs10837631; T > A), located on the 3′ β-globin gene [ 11 , 12 ]. Newly intragenic polymorphisms of the β-globin gene are informative polymorphisms in haplotype analysis associated with genetic background and clinical linkage studies of β-thalassemia mutations [ 13 , 14 , 15 ]. However, studies of these intergenic polymorphisms have yet to be comprehensively reported for the Thai population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thalassemia is an inherited autosomal recessive blood disorder that can be divided into either alpha (α) or beta (β) depending on the affected α or β globin chain [ 1 ]. The adult hemoglobin (HbA) consists of two α and two β (α2β2) chains in each HbA molecule [ 2 , 3 ]. Alpha-thalassemia occurs if one or more of the four alleles that code for α globin is missing or damaged [ 4 ].…”
Section: Thalassemia Syndromementioning
confidence: 99%
“…Thalassaemia is a group of inherited haematologic disorders caused by defects in the synthesis of one or more of the haemoglobin chains. These are among the most common genetic diseases globally, occurring more frequently in the Mediterranean, Indian subcontinent, Southeast Asia, and West Africa [1,2].…”
Section: Introductionmentioning
confidence: 99%